Palladium‐Catalyzed para‐C−H Arylation of Anilines with Aromatic Halides. Issue 47 (25th October 2022) - Lichte, Dominik; Pirkl, Nico; Heinrich, Gregor; Dutta, Sayan; Goebel, Jonas F.; Koley, Debasis; Gooßen, Lukas J.
Abstract: Controlling regioselectivity in C−H functionalizations is a key challenge in chemical method development. In arenes, functionalizations are most difficult to direct towards the C−H group furthest away from a substituent, in its para position. We herein demonstrate how the para ‐C−H arylation of anilines with non‐activated aryl halides, elusive to date, is achieved by a base‐assisted "metalla‐tautomerism" approach. A proton is abstracted from the aniline substrate and replaced by an arylpalladium species, generated from the aryl halide coupling partner. In this step, the palladium is directed away from the N ‐ to the tautomeric para ‐C−H position by a large phosphine ligand combined with a triphenylmethyl shielding group. The triphenylmethyl group is easily installed and removed, and can be recycled. Abstract : A selective para ‐C−H arylation of anilines with non‐activated aryl halides has been achieved by a metalla‐tautomerism approach. The reactivity of an aniline towards a palladium catalyst was relayed from the NH group into the aromatic ring. Out of four possible positions, the catalytic arylation was directed exclusively into the para ‐C−H position by a bulky ligand at the palladium in combination with a temporarily installed shielding group.